Study of Feeding Preference of Subterranean Termites (Coptotermes curvignathus Holmgren) on Wood Decaying Fungi - Yudi Rismayadi; Sri Hartati; Mustika Dewi (School of Life Sciences and Technology, Institut Teknologi Bandung, 2019)
Subterranean termites, Coptotermes curvignathus (Holmgren) is the most important termite which caused economic losses is very high in Indonesia and other tropical regions. In this studies, the feeding preferences of the subterranean termite, C. curvignathus for decayed wood by some wood rotting fungus were examined to determine whether the presence of wood rotting fungus could alter the relative preference of termites for these decayed wood. The study is expected to find phagostimulant compounds for the development of termite control by baiting techniques. The results showed that, the decayed wood process by the P. ostreotus fungi higher rate of decay compared with other fungus (10.86 + 2.21%), S. commune (10.29 + 1.86%), P. chrysosporium (6.19 +1.56%) and Dacriopinac sp (5.02 + 0.95%). Meanwhile, the lowest rate of decay by the T. versicolor fungi (4.25 + 0.93%). Based on the results of this stuies the feeding preference of C. curvigntahus on decayed wood by the P. ostreatus fungi and S. commune fungi is higher than the decayed wood by other wood rotting fungus.